Above‐ and below‐ground responses of four tundra plant functional types to deep soil heating and surface soil fertilization. (30th January 2017) - Wang, Peng; Limpens, Juul; Mommer, Liesje; van Ruijven, Jasper; Nauta, Ake L.; Berendse, Frank; Schaepman‐Strub, Gabriela; Blok, Daan; Maximov, Trofim C.; Heijmans, Monique M.P.D.
Summary: Climate warming is faster in the Arctic than the global average. Nutrient availability in the tundra soil is expected to increase by climate warming through (i) accelerated nutrient mobilization in the surface soil layers, and (ii) increased thawing depths during the growing season which increases accessibility of nutrients in the deeper soil layers. Both processes may initiate shifts in tundra vegetation composition. It is important to understand the effects of these two processes on tundra plant functional types. We manipulated soil thawing depth and nutrient availability at a Northeast‐Siberian tundra site to investigate their effects on above‐ and below‐ground responses of four plant functional types (grasses, sedges, deciduous shrubs and evergreen shrubs). Seasonal thawing was accelerated with heating cables at c. 15 cm depth without warming the surface soil, whereas nutrient availability was increased in the surface soil by adding slow‐release NPK fertilizer at c. 5 cm depth. A combination of these two treatments was also included. This is the first field experiment specifically investigating the effects of accelerated thawing in tundra ecosystems. Deep soil heating increased the above‐ground biomass of sedges, the deepest rooted plant functional type in our study, but did not affect biomass of the other plant functional types. In contrast, fertilization increased above‐ground biomass of the two dwarf shrub functional types, both of which had very shallow root systems. Grasses showed the strongest response to fertilization, both above‐ and below‐ground. Grasses were deep‐rooted, and they showed the highest plasticity in terms of vertical root distribution, as grass root distribution shifted to deep and surface soil in response to deep soil heating and surface soil fertilization respectively. Synthesis . Our results indicate that increased thawing depth can only benefit deep‐rooted sedges, while the shallow‐rooted dwarf shrubs, as well as flexible‐rooted grasses, take advantage of increased nutrient availability in the upper soil layers. Our results suggest that grasses have the highest root plasticity, which enables them to be more competitive in rapidly changing environments. We conclude that root vertical distribution strategies are important for vegetation responses to climate‐induced increases in soil nutrient availability in Arctic tundra, and that future shifts in vegetation composition will depend on the balance between changes in thawing depth and nutrient availability in the surface soil. Abstract : Our results indicate that increased thawing depth can only benefit deep‐rooted sedges, while the shallow‐rooted dwarf shrubs as well as flexible‐rooted grasses take advantage of increased nutrient availability in the upper soil layers. Our results suggest that grasses have the highest root plasticity, which enables them to be more competitive in rapidly changing environments. We conclude that root vertical distribution strategies are important for vegetation responses to climate‐induced increases in soil nutrient availability in Arctic tundra, and that future shifts in vegetation composition will depend on the balance between changes in thawing depth and nutrient availability in the surface soil.